Combined microbiomic and transcriptomic analysis revealed that dietary Clostridium autoethanogenum protein could improve the disease resistance of Litopenaeus vannamei by regulating the oxidative phosphorylation - Lili Shi; Xiaobo Yan; Zhao Yan; Hongming Wang; Jian Chen; Shuang Zhang (Aquaculture Reports)
Clostridium autoethanogenum protein (CAP) has been demonstrated to be a good protein ingredient for replacing fish meal (FM). In this study, an 8-week feeding experiment was conducted on L. vannamei (initial weight: 0.30 ± 0.02 g) with four isonitrogenous and isolipidic diets, which were designed with CAP substitution FM levels of 0 % (CON), 15 % (CAP15), 30 % (CAP30), and 45 % (CAP45), respectively. The results showed that dietary CAP substitution for FM had no influence on the feed coefficient rate (FCR) and survival rate (SR) of L. vannamei (P > 0.05), while the final body weight (FBW), special growth rate (SGR), and weight gain rate (WGR) of L. vannamei were significantly reduced than when the replacement ratio reached 30 % (P < 0.05). After Vibrio parahaemolyticus infection, significantly higher SR of L. vannamei was found in the CAP30 and CAP45 groups compared to CON group (P < 0.05). In the CAP substitution groups, the activities of superoxide dismutase (SOD), phenoloxidase (PO) were significantly increased while the contents of malondialdehyde (MDA) were significantly decreased (P < 0.05) in the serum of L. vannamei. Analysis of the intestinal microbiota showed that dietary CAP significantly changed the alpha diversity based on the indicators including Chao1, Simpson and ACE (P < 0.05). The compositions of the microbial communities in CAP substitution groups were significantly changed at phylum, family, and genus levels when compared to the CON group (P < 0.05), for the relative abundances of Planctomycetes, Firmicutes, Dadabacteria, Rubritaleaceae, Rubinisphaeraceae and Pir4_lineage were all remarkablely changed. Transcriptomic analysis showed that most of the differentially-expressed genes (DEGs) were enriched in metabolic processes (e.g., starch and sucrose metabolism, carbon metabolism, drug metabolism), oxidative phosphorylation and disease. Combined analysis of transcriptomic and microbiomic revealed that oxidative phosphorylation pathway-related gene expression was positively correlated with Rubritaleaceae while negatively correlated with Rubinisphaeraceae. Overall, the replacement of FM by CAP could improve the growth performance and disease resistance of L. vannamei, which probably by regulating the oxidative phosphorylation and the balance of intestinal microbiota.